Cystic fibrosis with multiple pulmonary arteriovenous malformations: A case report - Orito Ikeda, MD; Kunihiko Shimizu, MD; Yoshitake Yamada, PhD; Hiroaki Sugiura, MD; Hideaki Suzuki, MD; Syuichiro Umetsu, MD; Kozo Sato, MD; Masahiro Jinzaki, PhD (Radiology Case Reports, 2023)
Cystic fibrosis is an autosomal recessive genetic disorder that damages the exocrine function of the body, resulting in alterations of multiple organs. In the respiratory system, it is known to cause bronchiectasis, recurrent bronchitis, and pneumonia; however, to the best of our knowledge, there are no reported cases of pulmonary arteriovenous malformations associated with this disease. Herein, we report a case of cystic fibrosis with multiple pulmonary arteriovenous malformations. A 16-year-old girl, who has been monitored since childhood for pancreatitis of unknown cause, experienced respiratory symptoms and hypoxemia (PaO2 = 57 mmHg). At 13 years of age, chest computed tomography revealed bronchiectasis, bronchial wall thickening, and tree-in-bud sign. Genetic testing was performed, and the patient was diagnosed with cystic fibrosis. However, the computed tomography scan also showed incidental nodular lesions in the left superior and both the inferior pulmonary lobes, suggesting multiple arteriovenous malformations. Dynamic computed tomography was performed which, confirmed the presence of 3 pulmonary arteriovenous malformations. Coil embolization was performed on all lesions, and the hypoxemia was corrected. Marked hypoxemia in a patient with cystic fibrosis may not be explained only by the presence of bronchiectasis and/or bronchial wall thickening; in such cases, it may be necessary to examine possible additional findings on computed tomography images, such as arteriovenous malformations.